THE ROLE OF EFFICIENT MICROORGANISMS IN THE PROCESS OF OBTAINING THE BIOCOMPOST - Larisa CREMENEAC; Tatiana BOCLACI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the article are exposed the results of the study of biochemical quality of biocopmpost obtained by using the effective microorganisms from microbial preparations „Baikal ЭМ-1” and „EM-1”, in the process of bioconversion of the organic wastes unfermented. Material for research served unfermented cattle manure and the object of investigation - two preparations of efficient microorganisms „Baikal ЭМ-1” and „EМ-1”. Analyzing the results obtained in the experiment it was found that in biocompost obtained from the unfermented manure of cattle, subjected to the bioconversion process using preparations „Baikal ЭМ-1” and „EM-1” diminished essentially the content of ammonia, respectively with 79.68% - 70.91% and 85.09% - 70,03%, and increased the total nitrogen, respectively with 147.33% - 105.33% and 162.67% - 128.00% in comparison with the same indicators in manure samples at the initial stage. Consequently, it has been found that use „Baikal ЭМ-1” and „EM-1” preparations has led to substantial changes in content ammonia and total nitrogen, thus improving the quality of the biocompost.